Developing content and language integrated English speaking materials for accounting students - Dominique Savio Nsengiyumva (LingTera, 2018)
This study aimed at developing content and language integrated English speaking learning materials for the students of international accounting study program to help them learn, practise and improve their speaking skills first in content subjects classes and then in their future career. The study  involved 27 third year students of Accounting Department,  Faculty of Economics, Yogyakarta State University. The data were collected through an interview, classroom observation, and a students’ questionnaire. The research findings show that, the students prefer: business, accounting basics, accounting concepts, and financial accounting accounting contents topics. In terms of classroom activities, students preferred making presentations, discussion, dialogues, role-plays, and making descriptions. The students have difficulties in discussions/debates, pronunciation, grammatical structures, and knowledge of specific vocabulary items. Their priorities for speaking English include presentations, discussions, questions and answers, descriptions, and using specific vocabulary items. Their preferences on the components of the English speaking learning materials include conversations/dialogues, grammatical features, specific vocabulary items, presentations, and discussions/debates. The evaluation of the developed materials falls in the Very Good category for both experts and students’ evaluation.